Strengthening confidence, security building measures (CSBMs) in Southeast Asia: Asean in the post Covid-19 era - Ariesani Hermawanto,; Melaty Anggraini, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper discusses Confidence Security Building Measures (CSBMs) in Southeast Asia as an important tool and mechanism to create stability and build mutual understanding between ASEAN member states and countries outside the region. Using relevant primary and secondary data such as official government documents, books and journals, the study shows that CSBM mechanisms in the Southeast Asia region encourage surrounding countries to strengthen shared responsibilities and goals sustainably. The dialogue through CSBM’s mechanism emphasises cooperation and mutual understanding, which will further play an essential role in building a resilient and harmonious Southeast Asia. The study results show that the complexity of issues in the post-COVID-19 era requires strengthening CSBM through ASEAN with a focus on inclusivity and consensus building, constituting a mechanism of meaningful dialogue